2020
DOI: 10.1039/d0mt00220h
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between viral infections and trace elements from a metallomics perspective: implications for COVID-19

Abstract: Recently, the World Health Organization (WHO) declared a pandemic situation due to a new viral infection (COVID-19) caused by a novel virus (Sars-CoV-2). COVID-19 is today the leading cause of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 185 publications
(209 reference statements)
3
46
0
Order By: Relevance
“…Computational analysis has indicated that Zn-binding and Mn-binding domains are prevalent in viral proteomes and that many viral metal-binding proteins target host metal homeostasis regulators ( 227 ). The relevance of metal ions to the immune response to the SARS-CoV2—a cause of an unprecedented COVID-19 pandemic—has been discussed recently ( 228 ). As such, serum Fe levels have been linked to mortality risk in SARS-CoV2 patients ( 229 , 230 ).…”
Section: Adapting To Changes In Metal Availabilitymentioning
confidence: 99%
“…Computational analysis has indicated that Zn-binding and Mn-binding domains are prevalent in viral proteomes and that many viral metal-binding proteins target host metal homeostasis regulators ( 227 ). The relevance of metal ions to the immune response to the SARS-CoV2—a cause of an unprecedented COVID-19 pandemic—has been discussed recently ( 228 ). As such, serum Fe levels have been linked to mortality risk in SARS-CoV2 patients ( 229 , 230 ).…”
Section: Adapting To Changes In Metal Availabilitymentioning
confidence: 99%
“…Both trace element deficiency and excess lead to physiological disorders, and high metal concentrations can have toxic effects [10]. Trace elements play essential roles in the survival of the virus and the activation of the host's immune system [11]. For example, zinc (Zn) is antiviral against several viruses, necessary for the development of the immune system, and it inhibits the activity of the RNA-dependent RNA polymerase (RdRp) of the coronavirus [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that supplementation with vitamin D is a good preventive strategy in recurring respiratory tract infections [3] and also COVID-19 infections [20]. Furthermore, there is mounting evidence to suggest that balanced zinc, selenium, and vitamin C levels prevent viral respiratory infections [35][36][37][38][39][40]. Zinc is a dietary trace mineral that boosts immune cells [41].…”
Section: Introductionmentioning
confidence: 99%